PENGARUH PENAMPANG LINTANG PIPA PEMANASAN BAHAN BAKAR DENGAN MEDIA RADIATOR TERHADAP UNJUK KERJA MESINTOYOTA KIJANG 5K - Joko Suwondo; Bunawi Bunawi; Gatut Rubiono (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2014)
Fuel temperature has effect due to engine performance. This research is aimed to get the effect of cross section heating area with radiator heat due to performance of gasoline engine. The experiments are conduct in Toyota Kijang 5K gasoline engine. The radiator heat is use to raise the fuel temperature by 8 mm diameter copper pipe. The pipe is varied as round, oval and nearly flat. Fuel flow channel is place in the heat pipe with 900 mm of length which placed at upper tank of the radiator. The engine rotation speed is varied as 750, 1250, 1750 and 2250 rpm. Unheated fuel is use as a control. The research result shows the agreement that fuel temperature has effect due to fuel consumption. The result also shows that oval pipe has the lowest fuel consumption. Keywords: fuel temperature, copper pipe, fuel consumption, radiator’s upper tank